2010
DOI: 10.1271/bbb.100392
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Mulberry (Morus albaL.) Leaves on Hyperlipidemia in Rats Fed a High-Fat Diet: Induction of Fatty Acid Oxidation, Inhibition of Lipogenesis, and Suppression of Oxidative Stress

Abstract: To determine the effects of mulberry (Morus alba L.) leaves on hyperlipidemia, we performed gene expression profiling of the liver. Rats were fed a high-fat diet and administered mulberry leaves for 7 weeks. Plasma triglyceride and non-esterified fatty acid levels were significantly lower in the rats treated with mulberry leaves as compared with the untreated rats. DNA microarray analysis revealed that mulberry leaves upregulated expression of the genes involved in α-, β- and ω-oxidation of fatty acids, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 43 publications
10
67
1
1
Order By: Relevance
“…The activation of PPARa regulates lipoprotein metabolism, which enhances hepatic uptake and increases the esterification of free fatty acids (Fruchart and Duriez 2006) as well as activation of mitochondrial fatty acid oxidation. Kobayashi et al (2010) confirmed that mulberry had regulatory effects on the PPAR-mediated pathway, PPARa, and/or PPARd, which is involved in energy expenditure. Interestingly, a previous report suggested that supplementation with short-chain fatty acids (SCFA) reduced HFD-induced hepatic steatosis, but PPARc deficiency blocked the ameliorating effect of SCFA supplementation on hepatic steatosis by regulation of UCP2 and AMP-activated protein kinase (den Besten et al 2015).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The activation of PPARa regulates lipoprotein metabolism, which enhances hepatic uptake and increases the esterification of free fatty acids (Fruchart and Duriez 2006) as well as activation of mitochondrial fatty acid oxidation. Kobayashi et al (2010) confirmed that mulberry had regulatory effects on the PPAR-mediated pathway, PPARa, and/or PPARd, which is involved in energy expenditure. Interestingly, a previous report suggested that supplementation with short-chain fatty acids (SCFA) reduced HFD-induced hepatic steatosis, but PPARc deficiency blocked the ameliorating effect of SCFA supplementation on hepatic steatosis by regulation of UCP2 and AMP-activated protein kinase (den Besten et al 2015).…”
Section: Discussionmentioning
confidence: 66%
“…In our previous study, mulberry leaf has shown anti-inflammation and antioxidant effects on obesity (Lim et al 2013b). Earlier studies suggest some potential effects of the mulberry leaf on regulation of the antioxidant defense system and dyslipidemia in vivo and in vitro (Kobayashi et al 2010;Liu et al 2008;Peng et al 2011). In addition, mulberry leaf has several effects such as scavenging free radicals, inhibiting oxidation, and reducing atherogenic risk (Liu et al 2008).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The idea of employing flavonoids as plant-derived feed additives results from the wide spectrum of their physiological and pharmacological effects (Harborne and Williams, 2000;Khayyal et al, 2001;Githiori et al, 2006). Especially the antioxidant property of flavonoids and their ability to affect the activity of several metabolic enzymes are very promising in dairy cows, since they can experience oxidative stress during the peripartum period (Bernabucci et al, 2005;Kobayashi et al, 2010). Furthermore, flavonoid supplementation was shown to improve rumen fermentation parameters, limit the incidence of rumen acidosis (Balcells et al, 2012) and slightly increase the milk yield in dairy cows (Nielsen and Hansen, 2004;Gohlke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%